2015
DOI: 10.1016/j.cmet.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Insulin Resistance in the Mouse

Abstract: SUMMARY Insulin Resistance (IR) is a complex trait with multiple genetic and environmental components. Confounded by large differences between the sexes, environment and disease pathology, the genetic basis of IR has been difficult to dissect. Here we examine IR and related traits in a diverse population of more than 100 unique male and female inbred mouse strains after feeding a diet rich in fat and refined carbohydrates. Our results show dramatic variation in IR among strains of mice and widespread differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
221
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(225 citation statements)
references
References 52 publications
4
221
0
Order By: Relevance
“…In addition to prioritizing candidate genes, studies of natural variation in gene expression in mice should be useful in elucidating mechanisms relating to the gene-by-gene, gene-by-environment, and gene-by-sex interactions. 51,52,89 For example, although it is clear that genetic background contributes to weight gain and related traits in response to dietary challenge, 90 the inability to accurately ascertain environmental factors over a lifetime in humans has made molecular dissection difficult. In contrast, studies of natural variation in mice have revealed that gene-by-environment interactions can contribute substantially to the overall variance in traits such as obesity and that the underlying genes and pathways can be identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to prioritizing candidate genes, studies of natural variation in gene expression in mice should be useful in elucidating mechanisms relating to the gene-by-gene, gene-by-environment, and gene-by-sex interactions. 51,52,89 For example, although it is clear that genetic background contributes to weight gain and related traits in response to dietary challenge, 90 the inability to accurately ascertain environmental factors over a lifetime in humans has made molecular dissection difficult. In contrast, studies of natural variation in mice have revealed that gene-by-environment interactions can contribute substantially to the overall variance in traits such as obesity and that the underlying genes and pathways can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of natural variation in mice have revealed that gene-by-environment interactions can contribute substantially to the overall variance in traits such as obesity and that the underlying genes and pathways can be identified. 51,52 Whereas numerous studies have successfully mapped cis associations, few studies have reported trans-eQTLs because of small effect sizes, multiple testing thresholds, and computational burden. 22,37,91 These issues are consistent with the low reciprocal replication rates of trans-eQTLs identified in MuTHER and METSIM cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental design of the HF/ HS feeding study has also been described previously (25). Briefly, the female and male strains included in the HMDP study were maintained on a chow diet (Ralston Purina Co.) until 8 weeks of age before switching over to a HF/HS diet (Research Diet-D12266B; New Brunswick, NJ) for 8 weeks.…”
Section: Animal Proceduresmentioning
confidence: 99%